Agenda mediática comparativa entre medios públicos y privados sobre la aplicación de medidas arancelarias sobre los productos importados aplicados en el Ecuador - Peralta Rojas, Diana María (2015)
The present research seeks to make a mediatic analysis on the newspapers El Universo and El Telégrafo, about safeguards application that begun in march 2015 through executive order and applies to imported products. This measure was applied on 11th march 2015 on press conference offered by the Minister of Foreign Trade, Diego Aulestia, and the Coordinating Minister for Competitiveness and Production, Richard Espinoza, where it manifest the application of four new duties, the 32% of the imports will be in force 15 months which includes approximately 2.800 products, most of them are luxury types; while the 68%, which are Ecuadorian major consumption, are excluded. On this article the following questions were raised, ¿Which were the setting agenda used by the newspapers El Universo and El Telégrafo relating to the safeguards applied to the imported products on Ecuador 11th march 2015? ¿What type of political or social actors participated for the duties analysis, applied to the imported products on Ecuador 11th march 2015 On this way, it determinates that the social media pretend to control the political agenda through news coverage and generate influence on the public opinion from their target. The average of diary frequency of publications, allows identifying the ranking of the information and a logical explanation to the social media procedure